200 MeV Ag ion irradiation mediated green synthesis and self assembly of silver nanoparticles into dendrites for enhanced SERS applications. (April 2022) - Sherpa, Laden; Arun, Nimmala; Nageswara Rao, S.V.S.; Khan, S.A.; Pathak, A.P.; Tripathi, Ajay; Tiwari, Archana
Abstract: In this paper, we report green and controlled synthesis of silver nanoparticles in water with spherical, hetrogeneously shaped and extended chain like networks using pristine Bergenia ciliata root extracts and the extracts irradiated with Ag 15+ swift heavy ion irradiation. The ion fluence on the thin layer of extract modifies the phytomolecules responsible for the reduction and capping of the silver ion and thus changing the morphologies and sizes of the resultant nanoparticles. In addition, the irradiation assists the nanoparticles to agglomerate via surface oxidation providing a core for the growth of dendritic assemblies. Optical, crystallographic and morphological studies reveal surface oxidation of silver nanoparticles is enhanced upon the irradiation of the phytomolecules due to which the surface chemistry of the nanoparticles changes. In addition, these silver nanoparticles and their dendritic assembly exhibit high SERS enhancement factors for methylene blue analyte. The effects of irradiation promote the dendritic assemblies, roughened surfaces over the nanoparticle clusters and hence offer higher enhancement factors as compared to those which have been synthesized using pristine plant extracts. Highlights: Ag 15+ 200 MeV irradiation is used to modify Bergenia ciliate root extracts. These extracts are used to reduce AgNO3 in water into Ag nanoparticles. The reduction also yields hierarchical dendritic Ag nanostructures. The irradiation assists particles to agglomerate via surface oxidation. These nanostructures exhibits remarkable Raman signal of the dye via SERS.